The Political Economy of Financial Systems - Stephen Haber; Enrico Perotti (Tinbergen Institute, 2008)
This survey reviews the literature on the political economy of financial structure, broadly defined to include the size of capital markets and banking systems as well as the distribution of access to external finance across firms.The theoretical literature on the institutional basis for financial development and the recent evidence suggests that unconstrained political power undermines financial accumulation. Even under limited government, unaccountable institutions lead to regulatory capture, favor connected interests, and undermine finance access and entry. Thus the degree of access to political rights by citizens thus strongly affects their access to finance. Finally, we review the recent literature on the time variation of financial development across democracies during the XX century.
Keywords: G21; G28; G32; P16; 330; political institution; property rights; investor protection; financial development; access to finance; entry; banking; Politisches System; Finanzmarkt; Finanzmarktregulierung; Wirtschaftswachstum; Mexiko; USA